Field performance of somaclonal variants of plantain (Musa spp., AAB group) - Vuylsteke, D.R.; Swennen, Rony L.; Langhe, E. de (1996)
Four types of morphologically distinct somaclonal variants were identified in a population of False Horn plantain (Musa spp., AAB group) plants produced by in vitro shoot-tip culture. Field performance of these variants was compared with true-to-type plantain to evaluate their horticultural traits. Significant variation was observed for plant and fruit maturity, leaf size, yield and its components, but not for leaf number, plant height, or suckering. Three of the four somaclonal variants were horticulturally inferior to the original clone from which they were derived. Yields of these variants were very poor due to inflorescence degeneration or abnormal foliage. Only the `French reversion' variant, which resembled an existing cultivar, outyielded the true-to-type clone. However, its fruit weight and size were lower. Somaclonal variation through micropropagation is of limited use in plantain improvement as it mostly mimics naturally occurring variation along with the observed poor horticultural performance of somaclonal variants.